(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
In the recent years, the development of digital technology, the writing of letters, correspondence and various documents on a computer has created many conveniences in entering Chinese hieroglyphs on a computer or phone, it is no longer necessary to write hieroglyphs which are entered one by one in “pinyin” (Latinbased scripts). In fact, electronic or Internet dictionaries are widely used in the process of language learning. This, in turn, deteriorates the study of hieroglyphs and, moreover, written literacy.